Analisis Profil Kompetensi Literasi Sains Peserta Didik yang Diukur Menggunakan Instrumen Berbasis Kelas pada Materi Energi Terbarukan - Masithoh, Nadia Dewi; Jauhariyah, Mukhayyarotin Niswati Rodliyatul (Universitas Negeri Surabaya, 2024)
The following research aims to describe the analysis of students' scientific literacy profiles that have been developed. This scientific literacy profile analysis is in the form of scientific literacy levels based on scientific literacy competencies as well as a one-way ANOVA test in assessing scientific literacy based on renewable energy materials. This assessment instrument is used to measure students' competency abilities towards scientific literacy. The data analysis technique used uses quantitative descriptive analysis with score calculations at the level of scientific literacy. The scientific literacy profile of students as measured using the instrument developed resulted in a percentage of 13% categorized as very high, 54% categorized as high and 33% categorized as sufficient. The development of students' abilities was measured using the one way ANOVA test with a significant result (P Value) of 0.128 resulting in the criteria having no significant differences in the 3 classes regarding learning.